2017
DOI: 10.3892/or.2017.5558
|View full text |Cite
|
Sign up to set email alerts
|

miR-597 inhibits breast cancer cell proliferation, migration and invasion through FOSL2

Abstract: Many reports suggest that the discovery of microRNAs (miRNAs) might provide a novel therapeutical target for many diseases, even of human cancers; however, there are no reports on the role of miR-597 in human cancers. In the present study, by detecting mRNA expression with qRT-PCR, compared with the adjacent normal tissues we found that miR-597 was significantly downregulated in breast cancer tissues. By using the MTT assay, the cell wound-healing assay and the cell invasion assay, we demonstrated that miR-597… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…FOSL2 belongs to the activator protein 1 (activator protein, l, APl) transcription factor family 37 , 38 . FOSL2 is widespread in human tissues and plays an important role in mammalian growth, reproductive traits, and immune response 39 , 40 . The expression products of FOSL2 are related to cell adhesion, movement, invasion, metastasis and cell growth 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOSL2 belongs to the activator protein 1 (activator protein, l, APl) transcription factor family 37 , 38 . FOSL2 is widespread in human tissues and plays an important role in mammalian growth, reproductive traits, and immune response 39 , 40 . The expression products of FOSL2 are related to cell adhesion, movement, invasion, metastasis and cell growth 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression products of FOSL2 are related to cell adhesion, movement, invasion, metastasis and cell growth 37 . Studies have shown that over-expression of FOSL2 is associated with a higher invasive association with breast cancer and involved in breast cancer progression 39 . In addition, FOSL2 also plays a role in the TGF- beta signaling pathway, and is essential for TGF- beta1 to induce cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction was completed at 37°C for 60 min with PolyA primer, then the reaction solution was added to RT RNAase Free H 2 O to a total volume of 50 µl. Quantitative detection was completed according to the manufacturer's protocol as previously described ( 18 ) (miScript SYBR-Green PCR kit; Qiagen AB). The system included the following: 10 µl qRT-PCR-Mix, 0.5 µl forward primers and 0.5 µl reverse primers, 5 µl cDNA and 4 µl ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…18 Studies have shown that overexpression of FOSL2 is associated with higher migratory and invasive abilities in breast cancer, colon cancer, and hepatocellular carcinoma. [18][19][20] Very recent data have indicated that FOSL2 participates in OS cell proliferation, migration, and invasion. 21 Moreover, it has been reported that several miRNAs play a regulatory role by directly inhibiting target FOSL2 in cancers.…”
Section: Lncrna Linc00313 Knockdown Inhibits Tumorigenesis and Metastmentioning
confidence: 99%